Essential University Physics: Volume 1 (3rd Edition)

Published by Pearson
ISBN 10: 0321993721
ISBN 13: 978-0-32199-372-4

Chapter 4 - Exercises and Problems - Page 69: 67


a) $ \frac{(m_f-m_s)g}{m_s}$ b) $\frac{m_fa_sh_0}{(m_f-m_s)(g+a_s)}$

Work Step by Step

a) We know that the net forces must cancel if the spider is to climb without the fly falling. Thus, it follows: $m_sg+m_sa=m_fg\\ m_sa=m_fg-m_sg \\ m_sa=(m_f-m_s)g \\ a=\frac{(m_f-m_s)g}{m_s}$ b) We first find the value of a: $m_sa_s+m_sg=m_fg-m_fa$ $ a=\frac{(m_f-m_s)g-m_sa_s}{m_f}$ We know that $y=\frac{1}{2}a_st^2$. We find that the value of $t^2$ is: $t^2=\frac{2h_0}{a_s+a}$ Using substitution, it follows: $h=\frac{m_fa_sh_0}{(m_f-m_s)(g+a_s)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.